1989
DOI: 10.1056/nejm198904273201705
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Reoperation after Open and Transurethral Resection of the Prostate for Benign Prostatic Hyperplasia

Abstract: As part of an ongoing effort to evaluate alternative treatments for benign prostatic hyperplasia, we compared the outcomes of transurethral resection of the prostate with those of open prostatectomy. Men undergoing prostatectomy in Denmark (n = 36,703), Oxfordshire, England (n = 5284), and Manitoba, Canada (n = 12,090), were identified retrospectively through administrative data and followed for up to eight years. The cumulative percentage of patients undergoing a second prostatectomy was substantially higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
207
4
22

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 632 publications
(235 citation statements)
references
References 11 publications
2
207
4
22
Order By: Relevance
“…As seen in our results, most cases of BPH are treated by TUR rather than suprapubic prostatectomy, although studies have shown that chances of a patient undergoing another surgery for BPH is much higher after TUR than suprapubic prostatectomy (Roos et al, 1989). The mean weight of BPH specimens in our series was 19 grams for TUR and 43 grams for enucleation specimens.…”
Section: Discussionmentioning
confidence: 46%
“…As seen in our results, most cases of BPH are treated by TUR rather than suprapubic prostatectomy, although studies have shown that chances of a patient undergoing another surgery for BPH is much higher after TUR than suprapubic prostatectomy (Roos et al, 1989). The mean weight of BPH specimens in our series was 19 grams for TUR and 43 grams for enucleation specimens.…”
Section: Discussionmentioning
confidence: 46%
“…Medicare files have been used to study disease incidence and risk factors,1-3 to document regional variations in treatment patterns,4 5 to study hospital-associated mortality rates and quality of care,6 and to evaluate the outcomes of specific surgical and medical treatments. 7,8 Most concern about the validity of research findings based on the Medicare files has focused on issues related to the accuracy of diagnostic coding.9-" In this paper we highlight several other potential limitations of the Medicare data relevant to epidemiologic research by addressing two questions. First, can one assume that the population captured in Medicare files is the same as the elderly population of the United States?…”
Section: Introductionmentioning
confidence: 99%
“…Hemostaza se, među ostalim, postiže uz pomoć postavljanja balona trokrakog katetera u ležište prostate. Prednost otvorene prostatektomije pred transvezikalnom resekcijom prostate je manja učestalost ponovnog tretmana, kompletnije odstranjenje adenoma te izostanak TUR sindroma 10 . Nedostatak je potreba za incizijom trbušne stjenke, čime se produljuje poslijeoperativni oporavak, veća učestalost krvarenja koje zahtijeva trans fuziju, mogućnost ozljede sfinktera i rektuma te produljena urinarna kateterizacija 11 .…”
Section: Otvorena Jednostavna Prostatektomijaunclassified